THE IMPACT OF FLIPPED CLASSROOM ON EFL STUDENTS’ GRAMMATICAL COMPETENCE AND ATTITUDE IN CHINA - Liao Juan; Zurina Yasak (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aims to examine how flipped an English Grammar classroom would affect students’ English grammatical competence and attitude. The study was conducted for 6 weeks in two Business English classes of a vocational college in China. There are 50 students in the flipped classroom and 52 students in the traditional classroom. Achievement tests and a survey on learners’ attitudes of the model were used for collecting data. It was revealed the flipped classroom model exerted moderate impact on learners’ academic achievements compared to the traditional teaching methodology. Besides, students mostly had positive attitude towards applying the flipped classroom model in instructing English grammar.